Income inequality, TFP, and human capital - Sequeira, T. N.; Santos, M.; Ferreira-Lopes, A. (Economic Record, 2017)
A fruitful recent theoretical literature has related human capital and technological development to income (and wage) inequality. However, empirical assessments on the relationship are relatively scarce. We relate human capital, total factor productivity (TFP) and openness to inequality and discover that, when countries are assumed to be heterogeneous and dependent cross-sections, human capital is the most robust determinant of inequality, contributing to increasing inequality, as predicted by theory. TFP and openness turned out to be non-significantly related to inequality. These results are robust to a number of robustness tests on specifications and data and open up the prospect of theoretical research on the country-specific features conditioning the effect of human capital, technology and trade on inequality.